Experimental Study on Heat Transfer Process Optimization of Heat Storage Wall of the Heat Pump in Tunnel Surrounding Rock in the Cold Region - Yafei Li; Dianwei Qi; Hongchao Yan; Jiaqi Zhang (Geofluids)
For tunnels in cold or serious cold areas, the problem of leaking in the spring thawing period is very frequent, which will cause various tunnel diseases due to freezing. By using the surrounding rock geothermal energy in the tunnel project, especially the tunnel project below the permafrost layer, the cold area tunnel heat pump system is able to improve the overall heating energy efficiency as the side temperature regarding the heat pump evaporation increases, that furtherly serves the surrounding supporting building facilities. Inspired by this system and the active and passive coupling building technology, a heat recovery type of heat storage wall model is proposed in this research. By describing the heat transfer process regarding the heat recovery type of heat storage wall and carrying out the experimental research, its feasibility and effectiveness are verified. The results show that when the outdoor ambient temperature in Urumqi is −7~−15°C and the instantaneous total solar radiation reaches the range of 0~1108 W/m2, this kind of wall can create hot wall-near air whose temperature is 11.89°C higher than the ambient temperature for providing a high-quality air heat source for the air source heat pump when the temperature is low, thereby significantly improving the air source heat pump heating system efficiency. Without the photovoltaic and photothermal equipment, the heat recovery type of heat storage wall can make the utilization rate of solar energy reach 13% to 20%, even up to 36%.